Comparison Of Platelet Examination Results Automatic And Manual Method In Dengue Hemorrhagic Fever Patient Santa Elisabeth - Situmorang , Paska R; Sihotang, Lisbet Lasmaria; Napitupulu , David Sumanto (Jurnal EduHealth, 2022)
The number of casess of dengue hemorrhagic fever in indonesia is more than 2.5 billion cases that occur every year. Platelet examination can be done by 2 methods, namely automatic and manual. this study aims to determine whether there is a difference in the number of platelets between the automatic method (abx pentra 60), and the manual method (rees eecker). The research method used in an observational study with a cross sectional approach. The population in this study was 155 people, with a sample of 20 people and quota sampling technique. The inspection was carried out with an automatic abx pentra 60 and an improved neubauer. The results of the examination of flow pletelet counts using the automatic method obtained 1 sample (5.0%) and the manual method12 sample (60.0%) that difference between automatic and manual methods was 11 sample. The results of high automatic method of platelets were obtained by 4 sample (20.0%),and manual 3 sample(15.0%), that difference between two was obtained 1 sample. Comparison of the results automatic and manual platelet examination methods was p=0.004(p<0.005). the conclution from the results there were difference in the automatic method of checking the platelet count and the manual method in patients with dengue hemorrhagic fever.